Plasma mitochondrial DNA is associated with extrapulmonary sarcoidosis. Issue 2 (29th August 2019) - Ryu, Changwan; Brandsdorfer, Caitlin; Adams, Taylor; Hu, Buqu; Kelleher, Dylan W.; Yaggi, Madeleine; Manning, Edward P.; Walia, Anjali; Reeves, Benjamin; Pan, Hongyi; Winkler, Julia; Minasyan, Maksym; et al.
Sarcoidosis is an unpredictable granulomatous disease in which African Americans disproportionately experience aggressive phenotypes. Mitochondrial DNA (mtDNA) released by cells in response to various stressors contributes to tissue remodelling and inflammation. While extracellular mtDNA has emerged as a biomarker in multiple diseases, its relevance to sarcoidosis remains unknown. We aimed to define an association between extracellular mtDNA and clinical features of sarcoidosis. Extracellular mtDNA concentrations were measured using quantitative PCR for the human MT-ATP6 gene in bronchoalveolar (BAL) and plasma samples from healthy controls and patients with sarcoidosis from The Yale Lung Repository; associations between MT-ATP6 concentrations and Scadding stage, extrapulmonary disease and demographics were sought. Results were validated in the Genomic Research in Alpha-1 Antitrypsin Deficiency and Sarcoidosis cohort. Relative to controls, MT-ATP6 concentrations in sarcoidosis subjects were robustly elevated in the BAL fluid and plasma, particularly in the plasma of patients with extrapulmonary disease. Relative to Caucasians, African Americans displayed excessive MT-ATP6 concentrations in the BAL fluid and plasma, for which the latter compartment correlated with significantly higher odds of extrapulmonary disease. Enrichments in extracellular mtDNA in sarcoidosis are associated with extrapulmonary disease and African American descent. Further study into the mechanistic basis of these clinical findings may lead to novel pathophysiologic and therapeutic insights. Extrapulmonary sarcoidosis is a devastating disease phenotype that disproportionately affects African Americans. Enrichments in plasma mitochondrial DNA are seen in sarcoidosis and are associated with extrapulmonary disease and African American descent. http://bit.ly/2MHjAm6